A lithium iron manganese phosphate material and its synthesis method and use

Through layered stacking and sintering technology, the problem of low compaction density of lithium manganese iron phosphate material is solved, and a material with excellent particle size grading is formed, suitable for high-power applications, improving its performance in electric vehicles and other fields.

CN118954468BActive Publication Date: 2025-01-14TIANJIN GUOAN MGL NEW MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411419997.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The compaction density of lithium manganese iron phosphate (LMFP) material is low, which limits its commercial promotion in high-power applications such as electric vehicles, and poor conductivity affects its performance in high-power applications.

Method used

At least three lithium manganese iron phosphate precursors with different primary particle sizes are stacked and then uniformly sintered. The temperature and temperature field differences in the thickness direction are used to make the sintering effect of each layer differently, forming a bottom to the upper particle diameter The sintered material is increased in sequence, and the lithium manganese iron phosphate material mixed with large, medium and small particles is obtained by mixing and crushing, thereby improving the particle size grading and compaction density.

Benefits of technology

It significantly improves the compaction density of lithium manganese iron phosphate material, strengthens the particle size grading effect, improves the performance of the material, and is suitable for high-power applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the field of lithium-ion batteries. The present invention provides a lithium iron manganese phosphate material and a synthesis method and use thereof. The synthesis method comprises the following steps: performing layered stacking of at least three lithium iron manganese phosphate precursors with different primary particle sizes and then uniformly sintering them. The temperature and / or temperature field differences naturally generated along the thickness direction in the layered stacking are utilized to achieve different sintering effects for each layer, thereby obtaining a sintered material with increasing particle sizes from bottom to top. After the sintered materials are mixed and crushed, a lithium iron manganese phosphate material with large, medium and small particles mixed is formed, thereby enhancing the effect of particle size grading and greatly improving the compaction density of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries and relates to a lithium manganese iron phosphate material and a synthesis method and application thereof. Background Art

[0002] Since its introduction, lithium-ion batteries (LIBs) have played an indispensable role in portable electronic devices, electric vehicles (EVs) and large-scale energy storage systems (ESS) due to their high energy density, long cycle life and excellent power characteristics. Its working principle is based on the embedding and de-embedding process of lithium ions between positive and negative electrode materials, thereby realizing the storage and release of electrical energy. With the urgent market demand for higher performance batteries, the research and development of positive electrode materials has become the key to promoting the innovation of lithium-ion battery technology.

[0003] As the core component of lithium-ion batteries, the performance of cathode materials directly affects the capacity, safety and cost of batteries. Common cathode materials include lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt oxide (NMC), lithium nickel cobalt aluminum oxide (NCA) and lithium iron phosphate (LiFePO4, LFP). Among them, LFP has occupied a place in the low-end and mid-range battery market with its excellent thermal stability and cycle stability, as well as low cost and environmental friendliness.

[0004] The theoretical specific capacity of LFP positive electrode material is about 170mAh / g, which can reach about 160mAh / g in actual applications, and the operating voltage is about 3.4V. Its structural stability is good, and it is not easy to decompose even at high temperature or overcharge, ensuring the safety of the battery. However, LFP has poor conductivity, which limits its performance in high-power applications. In addition, the theoretical energy density of LFP is relatively low, which becomes a major shortcoming in application scenarios such as electric vehicles that have strict requirements on energy density.

[0005] In order to overcome the limitations of LFP, researchers turned their research direction to lithium manganese iron phosphate (LiMnFePO4, LMFP) materials. Although the theoretical specific capacity of LMFP is similar to that of LFP, about 170mAh / g, its operating voltage range is wider, up to 4.1V, which makes its theoretical energy density 10%~20% higher than that of LFP, which is particularly important for realizing high-power application conditions such as electric vehicles.

[0006] However, although the theoretical energy density of LMFP has been improved, the volume energy density of its battery cells has not been improved accordingly due to the low compaction density of the materials actually produced, which is usually between 2.2~2.3g / cm³, much lower than the 2.6~2.7g / cm³ of LFP, which seriously restricts its promotion in commercial applications.

[0007] In view of the limitations of LMFP materials in compaction density, the development of high-compacted LMFP cathode materials has become a hot topic in current research. Summary of the invention

[0008] In view of the problems existing in the prior art, the object of the present invention is to provide a lithium iron manganese phosphate material and a synthesis method and use thereof. The synthesis method is to perform layered stacking on at least three lithium iron manganese phosphate precursors with different primary particle sizes and then uniformly sinter them. The temperature and / or temperature field differences naturally generated along the thickness direction in the layered stacking are utilized to make the sintering effect of each layer different, thereby obtaining a sintered material with increasing particle size from bottom to top. After mixing and crushing them, a lithium iron manganese phosphate material with a mixture of large, medium and small particles is formed, which enhances the effect of particle size grading and greatly improves the compaction density of the material.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for synthesizing a lithium iron manganese phosphate material, the method comprising:

[0011] At least three lithium iron manganese phosphate precursors with different primary particle sizes are provided, and after being layered and stacked in a manner in which the primary particle sizes decrease from bottom to top, sintering is performed to obtain a sintered material with a particle size increasing from bottom to top, and the obtained sintered materials are mixed and crushed to obtain a lithium iron manganese phosphate material.

[0012] In the existing technology for preparing lithium manganese iron phosphate, the traditional process often uses precursors of the same particle size to sinter materials to obtain products, or sinter precursors of different particle sizes separately to obtain products, and then mix the products according to particle size grading. The present invention analyzes and studies the characteristics of actual production and manufacturing. Considering that the thickness of the material pile is relatively large during the actual sintering process, under the same sintering environment (referring to sintering in the same temperature zone of the same sintering equipment), there will usually be differences in heat conduction, heat radiation, temperature and temperature field in the thickness direction of the pile, resulting in differences in sintering effect along the thickness direction. The present invention utilizes this principle. Through research, a specific stacking method (or loading method) is used to stack precursors of different primary particle sizes in layers in a specific manner, with the layers in contact with each other, and then the layered pile is uniformly sintered under the same environment at the same time. The difference in sintering effect can be amplified to a level sufficient to affect the particle size of each layer of the pile after sintering.

[0013] Specifically, when the material is piled in layers in a way that the particle size decreases from bottom to top, the upper material is directly exposed to heat radiation, usually at a higher temperature. At the same time, the upper precursor has a small particle size and high reaction activity, and is easier to grow to form large particles of lithium iron manganese phosphate; similarly, the lower material is more difficult to grow and will form small particles of lithium iron manganese phosphate, and the middle material forms medium particles of lithium iron manganese phosphate, thereby obtaining a sintered material with a particle size increasing from bottom to top. After the sintered material is mixed and crushed, a lithium iron manganese phosphate material mixed with large, medium and small particles can be obtained, and the particle size grading is achieved in one step. Compared with the solution of particle size grading of lithium iron manganese phosphate in the prior art, the particle size grading effect achieved by the solution of the present invention is more excellent, and the compaction density is effectively improved.

[0014] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] As a preferred technical solution of the present invention, the synthesis method comprises:

[0016] Three lithium manganese iron phosphate precursors a, b and c with different primary particle sizes are provided, the primary particle sizes are Da, Db and Dc respectively, and (0.3~0.8)*Da=Db, for example, 0.3*Da=Db, 0.35*Da=Db, 0.4*Da=Db, 0.45*Da=Db, 0.5*Da=Db, 0.55*Da=Db, 0.6*Da=Db, 0.65*Da=Db, 0.7*Da=Db , 0.75*Da=Db or 0.8*Da=Db, etc.; and (0.3~0.8)*Db=Dc, for example, it can be 0.3*Db=Dc, 0.35*Db=Dc, 0.4*Db=Dc, 0.45*Db=Dc, 0.5*Db=Dc, 0.55*Db=Dc, 0.6*Db=Dc, 0.65*Db=Dc, 0.7*Db=Dc, 0.75*Db=Dc or 0.8*Db=Dc, etc.

[0017] As a preferred technical solution of the present invention, Da=150~200nm, for example, it can be 150nm, 155nm, 160nm, 165nm, 170nm, 175nm, 180nm, 185nm, 190nm, 195nm or 200nm, etc.; Db=80~120nm, for example, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm or 120nm, etc.; Dc=40~60nm, for example, 40nm, 42nm, 45nm, 48nm, 50nm, 53nm, 55nm, 58nm or 60nm, etc., and three primary particles are obtained respectively. The sintering materials A, B and C with different particle sizes have primary particle sizes DA, DB and DC respectively, and DA=30~100nm, for example 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm, etc., DB=150~200nm, for example 150nm, 160nm, 170nm, 180nm, 190nm or 200nm, etc., DC=350~600nm, for example 350nm, 380nm, 400nm, 420nm, 440nm, 460nm, 480nm, 500nm, 520nm, 540nm, 560nm, 580nm or 600nm.

[0018] As a preferred technical solution of the present invention, when the lithium manganese iron phosphate precursors a, b and c are layered and stacked, the corresponding bulk densities are ρa, ρb and ρc, respectively, forming material layers with thicknesses of Ha, Hb and Hc, respectively, and 0.9≤(ρa*Ha) / (ρc*Hc)≤1.1, for example, (ρa*Ha) / (ρc*Hc) can be 0.9, 0.93, 0.95, 0.98, 1, 1.02, 1 .05, 1.08 or 1.1, etc.; and 0.25≤(ρa*Ha+ρc*Hc) / (ρb*Hb)≤1, for example, (ρa*Ha+ρc*Hc) / (ρb*Hb) can be 0.25, 0.28, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or 1, etc.

[0019] As a preferred technical solution of the present invention, 0.1≤Ha / (Ha+Hb+Hc)≤0.3, for example, 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28 or 0.3, etc.; 0.4≤Hb / (Ha+Hb+Hc)≤0.8, for example, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75 or 0.8, etc.; 0.1≤Hc / (Ha+Hb+Hc)≤0.3, for example, 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28 or 0.3, etc.

[0020] As a preferred technical solution of the present invention, Ha+Hb+Hc=6~12cm, for example, it can be 6cm, 6.5cm, 7cm, 7.5cm, 8cm, 8.5cm, 9cm, 9.5cm, 10cm, 10.5cm, 11cm, 11.5cm or 12cm, etc.

[0021] In the present invention, in addition to the particle size of the precursor primary particles, on the one hand, the differences in temperature and temperature field in the material layer formed by layered stacking in the thickness direction must be considered, so thickness is one of the factors that mainly affect the sintering effect. On the other hand, it is also necessary to consider that the density of the material layer is different under different bulk densities, which will affect the bottom gas release and the heat radiation from the upper layer. Therefore, the thickness and bulk density are introduced for limitation. The present invention finds that placing highly active and small bulk materials in the upper layer is more conducive to the release of the bottom gas and the heat radiation of the upper layer to the lower layer.

[0022] As a preferred technical solution of the present invention, the method for preparing the lithium iron manganese phosphate precursor includes mixing a lithium source, an iron source, a manganese source, a phosphorus source, a carbon source and an additive to obtain a slurry, and then grinding and spray drying the slurry in sequence to obtain a lithium iron manganese phosphate precursor; and controlling the particle size of the primary particles of the obtained lithium iron manganese phosphate precursor by the grinding.

[0023] In the present invention, the particle size of the abrasive obtained by grinding determines the particle size of the primary particles of the precursor obtained after spray drying, and the particle size of the secondary particles of the precursor is mainly related to the spray parameters, and has little to do with the particle size of the primary particles of the abrasive. Therefore, the particle size of the primary particles of the lithium manganese iron phosphate precursor described in the present invention is the particle size of the primary particles of the abrasive obtained by grinding. By controlling the grinding to make the particle size of the primary particles of the precursor smaller, the reaction activity is higher, and the high temperature environment when in the upper layer is more conducive to the formation of large particles of lithium manganese iron phosphate, and vice versa.

[0024] Preferably, the grinding method comprises sand grinding.

[0025] It should be noted that the specific raw materials and amounts corresponding to the lithium source, iron source, manganese source, phosphorus source and carbon source used in the synthesis method of the present invention can be reasonably adjusted and selected according to actual conditions and needs. The specific raw materials, amounts and dosage ratios used in the prior art can be applicable to the present invention. As long as the synthesized product is a lithium iron manganese phosphate precursor and can be obtained by performing specific layered stacking and sintering according to the synthesis method of the present invention to obtain a lithium iron manganese phosphate material, the purpose of the present invention is met.

[0026] Exemplarily, the lithium source includes lithium carbonate; the iron source includes at least one of iron phosphate, ferromanganese phosphate or iron-containing oxides; the manganese source includes at least one of manganese phosphate, ferromanganese phosphate or manganese-containing oxides (such as manganese tetraoxide); the phosphorus source includes at least one of lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium phosphate or phosphoric acid; the carbon source includes at least one of glucose, polyethylene glycol, sucrose, citric acid, VC, graphene or carbon nanotubes; the additive includes at least one of magnesium oxide, titanium oxide, vanadium oxide, cobalt oxide or nickel oxide.

[0027] Exemplarily, the amounts of the lithium source, iron source, manganese source and phosphorus source are controlled according to the ratio of the molar amount of lithium element, the total molar amount of manganese element and iron element and the molar amount of phosphorus element (0.98~1.10):(0.96~1):1, for example, 0.98:0.96:1, 1.00:0.97:1, 1.02:0.98:1, 1.04:0.98:1, 1.06:0.99:1, 1.08:0.99:1, 1.1:0.99:1, 1.1:1:1, etc.

[0028] Exemplarily, the amounts of the iron source and the manganese source are controlled according to the ratio of the molar amount of manganese element to the molar amount of iron element (1.0~4.0):1, for example, 1.0:1, 1.3:1, 1.6:1, 2.0:1, 2.3:1, 2.6:1, 3.0:1, 3.3:1, 3.6:1 or 4.0:1, etc.

[0029] Exemplarily, the amount of the carbon source is controlled according to the mass ratio of the carbon source to the theoretical production of lithium iron manganese phosphate (0.08-0.12):1, for example, 0.08:1, 0.084:1, 0.088:1, 0.092:1, 0.096:1, 0.10:1, 0.104:1, 0.108:1, 0.112:1, 0.116:1 or 0.12:1, etc.

[0030] As a preferred technical solution of the present invention, the mixing also uses additives. By adding metal oxide additives, the capacity and rate performance of the material can often be improved.

[0031] Preferably, the additive includes at least one of magnesium oxide, titanium oxide, vanadium oxide, cobalt oxide or nickel oxide.

[0032] Preferably, the amount of the additive is controlled according to a mass ratio of the additive to the theoretical amount of lithium manganese iron phosphate produced of (0.0005-0.01):1, for example, 0.0005:1, 0.0008:1, 0.001:1, 0.002:1, 0.003:1, 0.004:1, 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1 or 0.01:1, etc.

[0033] As a preferred technical solution of the present invention, the sintering equipment includes a box furnace and / or a roller kiln.

[0034] It should be noted that the sintering process of the synthesis method described in the present invention can be carried out in conventional sintering equipment, because the present invention utilizes the difference in sintering effect along the thickness direction of the pile of large thickness in conventional sintering equipment. Generally speaking, the top temperature of conventional sintering equipment such as roller kilns and / or box furnaces along the height of the sagger is 10~30℃ higher than the bottom temperature. Even so, only using a uniform single precursor to sinter the upper particles is not large enough, and the lower particles are not small enough. It is also impossible to form the favorable effect of the present invention that the upper material is loose and small, and the loose and porous upper material forms a smooth discharge of the gas produced by the sintering of the lower material. It is difficult to form an effective particle size distribution, and it is impossible to effectively improve compaction and product performance.

[0035] As a preferred technical solution of the present invention, the sintering is carried out in an inert atmosphere; the heating rate of the sintering is 1-5°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min; the sintering includes first sintering at 300-500°C, such as 300°C, 330°C, 350°C, 380°C, 400°C, 430°C, 450°C, 480°C or 500°C, and then The first sintering is performed for 4 to 6 hours, for example, 4h, 4.3h, 4.5h, 4.8h, 5h, 5.3h, 5.5h, 5.8h or 6h, and then the second sintering is performed at 700-750°C, for example, 700°C, 710°C, 720°C, 730°C, 740°C or 750°C for 4 to 6 hours, for example, 4h, 4.3h, 4.5h, 4.8h, 5h, 5.3h, 5.5h, 5.8h or 6h.

[0036] As a preferred technical solution of the present invention, the mixed pulverizing method includes air flow pulverizing.

[0037] In a second aspect, the present invention provides a lithium manganese iron phosphate material obtained according to the synthesis method described in the first aspect.

[0038] The lithium iron manganese phosphate material obtained by the synthesis method described in the first aspect of the present invention directly obtains an excellent particle size grading effect. For example, when the primary particle size of the lithium iron manganese phosphate precursor used is Da=150~200nm, Db=80~120nm and Dc=40~60nm, the synthesis method can be used to form a small particle sintered material product with a primary particle size of 30~100nm (i.e., the above-mentioned DA), a medium particle sintered material product with a primary particle size of 150~200nm (i.e., the above-mentioned DB), and a large particle sintered material product with a primary particle size of 350~600nm (i.e., the above-mentioned DC). The sintering process of the material is a process of lithium ion diffusion and nucleation growth at the same time. The small particle size precursor is conducive to the internal diffusion of lithium salts, and the single crystal grows faster, while the large particle precursor is difficult for lithium ions to diffuse. Due to phase separation during the solid phase reaction, a positive electrode material with a primary particle size lower than the precursor can even be formed. After mixed and crushed, a lithium iron manganese phosphate material with a particle size gradation is formed. It should be noted that the particle size of the primary particles can be measured by the observation value under a scanning electron microscope. The lithium iron manganese phosphate material is basically an agglomerate (secondary particle). The particle size of the agglomerate is related to the degree of crushing. Therefore, the value measured by the particle size tester is not the particle size of the primary particles, but the particle size tester can be used to monitor the overall D50 particle size of the lithium iron manganese phosphate material obtained after mixed crushing, so as to affect the particle size of the primary particles of the precursor by adjusting the particle size of the abrasive, etc., and the precursor with suitable particle sizes can be selected for matching, and / or the sintering conditions can be adjusted to achieve the overall D50 particle size. For example, if the overall D50 particle size of the obtained lithium iron manganese phosphate material is to be increased, the particle size of the abrasive is reduced, so that Da, Db and Dc are all reduced, so that the overall D50 of the precursor becomes smaller, and / or the sintering temperature provided by the sintering equipment is appropriately increased during sintering.

[0039] In a third aspect, the present invention provides a lithium-ion battery comprising the lithium iron manganese phosphate material described in the second aspect.

[0040] Due to space limitations and to avoid redundancy, the present invention does not exhaustively list all point values ​​within the above numerical range, but is not limited to the listed values, and values ​​not listed within the above numerical range are equally applicable.

[0041] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0042] The present invention fully considers the actual stacking state and its influence on crystal growth in the sintering process of the actual synthesis of lithium iron manganese phosphate material. At least three lithium iron manganese phosphate precursors with different primary particle sizes are layered and then sintered uniformly. The temperature and / or temperature field differences naturally generated along the thickness direction in the layered stacking are utilized to make the sintering effect of each layer different, so that the high-activity small-particle-size precursor particles of the upper material layer grow under high temperature and high heat to produce a larger product particle size, and the low-activity large-particle-size precursor particles of the lower material layer grow under low temperature and low heat to produce a smaller product particle size, thereby obtaining a sintered material with increasing particle size from bottom to top. After mixing and crushing them, a lithium iron manganese phosphate material with a mixture of large, medium and small particles is formed, thereby enhancing the effect of particle size grading and greatly improving the compaction density of the material. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0044] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.

[0045] Example 1

[0046] This embodiment provides a method for synthesizing lithium manganese iron phosphate material, comprising:

[0047] (1) mixing iron ferric phosphate as an iron source, manganese tetraoxide as a manganese source, lithium dihydrogen phosphate as a phosphorus source, lithium carbonate as a lithium source, glucose as a carbon source, polyethylene glycol and magnesium oxide as an additive, controlling the amounts of lithium, iron source, manganese source and phosphorus source according to the ratio of the molar amount of lithium element, the total molar amount of manganese element and iron element and the molar amount of phosphorus element being 1.02:0.98:1, controlling the amounts of the manganese source and the iron source according to the ratio of the molar amount of manganese element to the molar amount of iron element being 1.5:1, controlling the masses of glucose, polyethylene glycol and magnesium oxide as an additive to account for 5%, 5% and 0.2% (i.e. 2000 ppm) of the theoretical amount of lithium manganese iron phosphate, respectively, to obtain a slurry;

[0048] (2) The slurry was then sand-milled and the morphology was tested. When the primary particle size was 170 nm, a portion of the material was taken out and spray-dried to obtain precursor a (i.e., the primary particle size of precursor a was Da = 170 nm). The bulk density of precursor a was tested to be ρa = 1.0 g / cm 3 Then continue sand grinding until the primary particle size is 100nm, take out part of the material and spray dry it to obtain precursor b (i.e. the primary particle size of precursor b is Db=100nm), the bulk density of material b is ρb=0.94g / cm 3The remaining material was sand-milled until the primary particle size was 50 nm, and then the sand-milling was stopped. The precursor c was obtained by spray drying (i.e., the primary particle size of the precursor c was Dc = 50 nm). The bulk density of the precursor c was ρc = 0.85 g / cm 3 ; At this time, 0.59Da=Db, 0.5Db=Dc;

[0049] (3) Put each precursor into a pot, and stack precursor a, precursor b and precursor c in layers from bottom to top to form material layer a, material layer b and material layer c respectively. The thickness of material layer a, material layer b and material layer c are controlled to be Ha=2cm, Hb=5.65cm and Hc=2.35cm respectively. At this time, Ha+Hb+Hc=10, Ha / (Ha+Hb+Hc)=0.2, Hb / (Ha+Hb+Hc)=0.565, Hc / (Ha+Hb+Hc)=0.235, (ρa*Ha) / (ρc*Hc)=1.001, (ρa*Ha+ρc*Hc) / (ρb*Hb)=0.753;

[0050] (4) The layered pile is placed in a box furnace and sintered in a nitrogen atmosphere. The heating rate is controlled to be 2.5°C / min. The first sintering is carried out at 400°C for 5 hours, and then the second sintering is carried out at 720°C for 5 hours. After the sintering is completed, sintered materials A, B and C with increasing particle sizes from bottom to top are obtained. The primary particle sizes are DA=70nm, DB=170nm, and DC=500nm, respectively. All the sintered materials are uniformly and simultaneously subjected to air flow crushing to obtain lithium manganese iron phosphate material.

[0051] Example 2

[0052] This embodiment provides a method for synthesizing lithium iron manganese phosphate material. In step (3) of the synthesis method, the thicknesses of material layer c, material layer b and material layer a are controlled to be Hc=0.94 cm, Hb=2.26 cm and Ha=0.8 cm respectively, so that Ha+Hb+Hc=4. Except for the above, other conditions are exactly the same as those in Example 1.

[0053] Example 3

[0054] This embodiment provides a method for synthesizing lithium iron manganese phosphate material. In step (3) of the synthesis method, the thicknesses of material layer a, material layer b and material layer c are controlled to be Ha=1.2 cm, Hb=3.39 cm and Hc=1.41 cm respectively, so that Ha+Hb+Hc=6. Except for the above, other conditions are exactly the same as those in Example 1.

[0055] Example 4

[0056] This embodiment provides a method for synthesizing lithium iron manganese phosphate material. In step (3) of the synthesis method, the thicknesses of material layer a, material layer b and material layer c are controlled to be Ha=2.4 cm, Hb=6.78 cm and Hc=2.82 cm respectively, so that Ha+Hb+Hc=12. Except for the above, other conditions are exactly the same as those in Example 1.

[0057] Example 5

[0058] This embodiment provides a method for synthesizing lithium iron manganese phosphate material. In step (3) of the synthesis method, the thicknesses of material layer a, material layer b and material layer c are controlled to be Ha=3 cm, Hb=8.48 cm and Hc=3.52 cm respectively, so that Ha+Hb+Hc=15. Except for the above, other conditions are exactly the same as those in Example 1.

[0059] Example 6

[0060] This embodiment provides a method for synthesizing lithium iron manganese phosphate material. In step (3) of the synthesis method, the thicknesses of material layer a, material layer b and material layer c are controlled to be Ha=0.92 cm, Hb=8.2 cm and Hc=0.88 cm respectively, so that Ha / (Ha+Hb+Hc)=0.092, Hb / (Ha+Hb+Hc)=0.82, Hc / (Ha+Hb+Hc)=0.088, (ρa*Ha) / (ρc*Hc)=1.23, (ρa*Ha+ρc*Hc) / (ρb*Hb)=0.216, but Ha+Hb+Hc=10 remains unchanged. Except for the above, other conditions are exactly the same as those in Example 1.

[0061] Example 7

[0062] This embodiment provides a method for synthesizing lithium iron manganese phosphate material. In step (3) of the synthesis method, the thicknesses of material layer a, material layer b and material layer c are controlled to be Ha=1 cm, Hb=7.8 cm and Hc=1.2 cm respectively, so that Ha / (Ha+Hb+Hc)=0.1, Hb / (Ha+Hb+Hc)=0.78, Hc / (Ha+Hb+Hc)=0.12, (ρa*Ha) / (ρc*Hc)=0.98, (ρa*Ha+ρc*Hc) / (ρb*Hb)=0.276, but Ha+Hb+Hc=10 remains unchanged. Except for the above, other conditions are exactly the same as those in Example 1.

[0063] Example 8

[0064] This embodiment provides a method for synthesizing lithium iron manganese phosphate material. In step (3) of the synthesis method, the thicknesses of material layer a, material layer b and material layer c are controlled to be Ha=2.45 cm, Hb=4.7 cm and Hc=2.85 cm respectively, so that Ha / (Ha+Hb+Hc)=0.245, Hb / (Ha+Hb+Hc)=0.47, Hc / (Ha+Hb+Hc)=0.285, (ρa*Ha) / (ρc*Hc)=1.011, (ρa*Ha+ρc*Hc) / (ρb*Hb)=1.103, but Ha+Hb+Hc=10 remains unchanged. Except for the above, other conditions are exactly the same as those in Example 1.

[0065] Example 9

[0066] This embodiment provides a method for synthesizing lithium iron manganese phosphate material. In step (3) of the synthesis method, the thicknesses of material layer a, material layer b and material layer c are controlled to be Ha=3 cm, Hb=4 cm and Hc=3 cm respectively, so that Ha / (Ha+Hb+Hc)=0.3, Hb / (Ha+Hb+Hc)=0.4, Hc / (Ha+Hb+Hc)=0.3, (ρa*Ha) / (ρc*Hc)=1.176, (ρa*Ha+ρc*Hc) / (ρb*Hb)=1.476, but Ha+Hb+Hc=10 remains unchanged. Except for the above, other conditions are exactly the same as those in Example 1.

[0067] Example 10

[0068] This embodiment provides a method for synthesizing a lithium iron manganese phosphate material. In step (4) of the synthesis method, the temperature of the first sintering is adjusted to 270° C., and the temperature of the second sintering is adjusted to 670° C. Except for the above, other conditions are exactly the same as those in Example 1.

[0069] Embodiment 11

[0070] This embodiment provides a method for synthesizing lithium iron manganese phosphate material. In step (4) of the synthesis method, the temperature of the first sintering is adjusted to 300° C., and the temperature of the second sintering is adjusted to 700° C. Except for the above, other conditions are exactly the same as those in Example 1.

[0071] Example 12

[0072] This embodiment provides a method for synthesizing lithium iron manganese phosphate material. In step (4) of the synthesis method, the temperature of the first sintering is adjusted to 500° C., and the temperature of the second sintering is adjusted to 750° C. Except for the above, other conditions are exactly the same as those in Example 1.

[0073] Example 13

[0074] This embodiment provides a method for synthesizing a lithium iron manganese phosphate material. In step (4) of the synthesis method, the temperature of the first sintering is adjusted to 530° C., and the temperature of the second sintering is adjusted to 780° C. Except for the above, other conditions are exactly the same as those in Example 1.

[0075] Comparative Example 1

[0076] This comparative example provides a method for synthesizing lithium iron manganese phosphate material. In the method, no layered stacking is performed in step (3). Precursors a, b and c are mechanically mixed in the same amounts as in Example 1 to obtain precursor d. The obtained precursor d is then potted and sintered in step (4). Except for the above, other conditions are exactly the same as in Example 1.

[0077] Comparative Example 2

[0078] This comparative example provides a method for synthesizing a lithium iron manganese phosphate material. In the method, the slurry is sand-milled in step (2) to obtain three types of abrasives having primary particle sizes of 170 nm, 100 nm and 50 nm, respectively; the three types of abrasives are mechanically mixed in the same amount as in Example 1 to obtain a mixed slurry; the mixed slurry is spray-dried to obtain a precursor e; the obtained precursor e is potted in step (3) and sintered in step (4). Except for the above, the other conditions are exactly the same as in Example 1.

[0079] Comparative Example 3

[0080] This comparative example provides a method for synthesizing a lithium iron manganese phosphate material. In the method, no layered stacking is performed in step (3). Instead, the precursors a, b and c are respectively potted in the same amounts as in Example 1 and then sintered in step (4) to obtain three types of lithium iron manganese phosphate materials. The three types of lithium iron manganese phosphate materials are mechanically mixed to obtain lithium iron manganese phosphate materials with particle size distribution. Except for the above, other conditions are exactly the same as in Example 1.

[0081] Comparative Example 4

[0082] This comparative example provides a method for synthesizing a lithium iron manganese phosphate material. In the synthesis method, in step (3), the method adjusts the way of stacking the precursors in layers, so that from bottom to top, precursor c, precursor b and precursor a are stacked in layers to form material layer c, material layer b and material layer a respectively, that is, the primary particle size of the precursors increases from bottom to top. Except for the above, other conditions are exactly the same as those in Example 1.

[0083] Comparative Example 5

[0084] This comparative example provides a method for synthesizing lithium iron manganese phosphate material. In the method, no layered stacking is performed in step (3). Only precursor b is used for filling and then sintering in step (4). Except for the above, other conditions are exactly the same as those in Example 1.

[0085] Characterization and Testing:

[0086] Ⅰ. The compaction density test was performed on the lithium manganese iron phosphate materials obtained in the embodiment and the comparative example. The results are shown in Table 1.

[0087] II. The lithium manganese iron phosphate materials obtained in the examples and comparative examples were prepared into positive electrode sheets and then the discharge capacity was tested. The results are shown in Table 1.

[0088] Table 1

[0089] Group 0.1C discharge specific capacity (mAh / g) <![CDATA[3T powder compaction (g / cm 3 )]]> Example 1 155.2 2.45 Example 2 149.3 2.38 Example 3 152.1 2.4 Example 4 153.2 2.42 Example 5 151.2 2.31 Example 6 152.4 2.32 Example 7 153.4 2.36 Example 8 151.4 2.33 Example 9 150.2 2.29 Example 10 149.8 2.28 Embodiment 11 151.4 2.38 Example 12 149.7 2.41 Example 13 149.1 2.40 Comparative Example 1 149.3 2.23 Comparative Example 2 149.2 2.26 Comparative Example 3 148.4 2.33 Comparative Example 4 148.3 2.18 Comparative Example 5 148.6 2.15

[0090] It can be seen from Table 1 that:

[0091] Comparing Examples 1-5, under the same lithium manganese iron phosphate precursor, Example 2 has a total thickness when stacking that is too small, which will cause the overall growth of particles to be larger, increase the electrochemical impedance of the material in the battery, and cause a low capacity. Example 5 has a total thickness when stacking that is too large, resulting in smaller particles as a whole and lower compaction. At the same time, the large particles at the bottom have poor reactivity and are too thick, resulting in insufficient reaction of the bottom materials and a slightly reduced capacity.

[0092] Comparing Example 1 and Examples 6-9, under the same total pile thickness, the proportion of large and small particle precursors in Example 6 is too small, resulting in low compaction, and there are too many large and small particles in Examples 8 and 9. Too many small particles will cause loose particles and affect the compaction of the material to a certain extent, so Example 9 has the lowest compaction. Excessive large particles will affect the performance of the material capacity, so compared with Example 1, its capacity is also lower.

[0093] Comparing Example 1 with Examples 10-13, by adjusting the sintering conditions, the particle size can also be affected, thereby affecting the performance of the material. Compared with Example 1, Example 10 has a low sintering temperature and too small particles, resulting in a compaction weight of only 2.28 g / cm 3, its capacity is also lower than that of Example 1 due to the low sintering temperature and poor material crystallinity. As the temperature increases, compared with Example 10, the capacity and compaction of Example 11 both tend to increase gradually. The compaction increases because the sintered material particles increase, and the capacity increases because the material crystallinity gradually improves. The compaction and capacity increase of Example 1 compared with Example 11 are the same. As the temperature of the two insulation platforms of Examples 12-13 further increases, the small and large particle precursors grow too large, and the compaction does not further increase. At the same time, the oversized particles also affect the ionic conductivity of the material in the battery, and the capacity becomes worse and worse.

[0094] In comparative example 1, precursors a, b and c obtained by spray drying are uniformly mixed to obtain precursor d, and in comparative example 2, precursor e is uniformly spray-dried after mixing the grinding materials. Although it seems that several materials with different particle sizes have undergone particle size grading, they are not the sintering process after layered stacking. From the overall point of view, both of them are still formed in advance as a uniform material before sintering, and in the sintering process, grain growth is originally a fusion process. Therefore, the precursors with different primary particle sizes in comparative examples 1 and 2 will still be fused into lithium iron manganese phosphate particles of uniform size. Therefore, the compaction and improvement of the lithium iron manganese phosphate materials obtained by the two are not obvious. However, the present invention, as in Example 1, uses different raw material precursors for layered stacking and sintering, and the design of the size particle grading can be maintained after sintering, so the compaction of the obtained lithium iron manganese phosphate material is relatively high.

[0095] Comparative Example 3 is to sinter different precursors separately and then mix them, which can form a certain particle size distribution and mixing effect, and the compaction is slightly improved. However, it does not utilize different pile thicknesses (filling depths) and different material looseness like the present invention, and then cooperate with differences in sintering effects such as temperature and temperature difference to form better growth of large and small particles, as well as better gas release. Therefore, its capacity and compaction are slightly worse than those of the present invention.

[0096] Comparative Example 4 changes the arrangement of lithium iron manganese phosphate precursors a, b, and c, with large-particle lithium iron manganese phosphate precursor a placed on the upper layer and small-particle lithium iron manganese phosphate precursor c placed on the lower layer. This results in the positive electrode material sintered from the high-activity small-particle precursor being smaller than that in Example 1, and the positive electrode material sintered from the low-activity large-particle precursor being larger than that in Example 1, which is completely opposite to the desired sintering effect of the present invention, resulting in lower powder compaction than in Example 1.

[0097] Comparative Example 5 only uses precursor b for sintering, and its particle size distribution is the worst, resulting in the worst powder compaction, which is only 2.15g / cm 3 .

[0098] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0099] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0100] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for synthesizing lithium manganese iron phosphate material, characterized in that: The synthesis method comprises: At least three lithium iron manganese phosphate precursors with different primary particle sizes are provided, including three lithium iron manganese phosphate precursors a, b and c with different primary particle sizes, the primary particle sizes are Da, Db and Dc respectively, and (0.3~0.8)*Da=Db, (0.3~0.8)*Db=Dc; layered stacking is performed in a manner in which the primary particle sizes decrease from bottom to top, wherein the lithium iron manganese phosphate precursors a, b and c have corresponding bulk densities of ρa, ρb and ρc respectively when layered stacking is performed, forming material layers with thicknesses of Ha, Hb and Hc respectively, and 0.9≤(ρa*Ha) / (ρc*Hc)≤1.1, 0.25≤(ρa*Ha+ρc*Hc) / (ρb*Hb)≤1; then sintering is performed to obtain a sintered material with a particle size increasing from bottom to top, and the obtained sintered material is mixed and crushed to obtain a lithium iron manganese phosphate material.

2. The synthesis method according to claim 1, characterized in that Da=150~200nm; Db=80~120nm; Dc=40~60nm; corresponding to three sintering materials A, B and C with different primary particle sizes, the primary particle sizes are DA, DB and DC, and DA=30~100nm, DB=150~200nm, DC=350~600nm.

3. The synthesis method according to claim 1, characterized in that 0.1≤Ha / (Ha+Hb+Hc)≤0.3; 0.4≤Hb / (Ha+Hb+Hc)≤0.8; 0.1≤Hc / (Ha+Hb+Hc)≤0.3; Ha+Hb+Hc=6~12cm.

4. The synthesis method according to claim 1, characterized in that The method for preparing the lithium iron manganese phosphate precursor includes mixing a lithium source, an iron source, a manganese source, a phosphorus source and a carbon source to obtain a slurry, and then grinding and spray drying the slurry in sequence to obtain a lithium iron manganese phosphate precursor; and controlling the particle size of the primary particles of the obtained lithium iron manganese phosphate precursor by grinding.

5. The synthesis method according to claim 4, characterized in that The mixing also uses additives; The additive includes at least one of magnesium oxide, titanium oxide, vanadium oxide, cobalt oxide or nickel oxide; The amount of the additive is controlled according to the mass ratio of the additive to the theoretical amount of lithium manganese iron phosphate produced (0.0005~0.01):

1.

6. The synthesis method according to claim 1, characterized in that The sintering equipment includes a box furnace and / or a roller kiln; The sintering is carried out in an inert atmosphere; the heating rate of the sintering is 1-5°C / min; the sintering includes first sintering at 300-500°C for 4-6h, and then second sintering at 700-750°C for 4-6h; The mixed pulverization method includes air flow pulverization.

7. A lithium manganese iron phosphate material, characterized in that: Obtained according to the synthesis method according to any one of claims 1 to 6.

8. A lithium ion battery, characterized in that: Contains the lithium manganese iron phosphate material as claimed in claim 7.

Citation Information

Patent Citations

  • Preparation method of high-compaction lithium manganese iron phosphate positive electrode material for lithium ion battery

    CN115010108A

  • Preparation method and application of lithium manganese iron phosphate

    CN115231541A